Xanthomatous hypophysitis behaving like pituitary adenoma - MA Xiao⁃li; TONG Jia⁃jie; ZHANG Xiu⁃zhi; DU Qian; SUI Ai⁃xia; ZHAO Huan⁃fen (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Objective To report a case of xanthomatous hypophysitis (XH), and summarize its clinical manifestations, laboratory, imaging and histopathological features. Methods and Results The patient was a male XH diagnosed and treated by Hebei General Hospital in July 2018. The clinical manifestations were headache with nausea and vomiting. Head CT showed the sella area was dense and full; MRI showed enlargement of the sella and a type of circular mass within the sella. The clinical diagnosis was pituitary adenoma apoplexy, and pituitary adenoma resection was performed through nasal sphenoid approach under neuroendoscopy. The postoperative pathological examination showed the histopathological cells showed flake dense infiltration, the immunohistochemical staining showed strong positive CD68 and vimentin (Vim), and S ⁃100 protein and CD1α were negative, Ki⁃67 antigen labeling index was 10%-20%, and the final diagnosis was sellar XH. Conclusions XH is rare in clinic, and its symptoms and imaging findings are nonspecific, making clinical diagnosis extremely challenging. Neuroendoscopic biopsy pathology is the "gold standard" for diagnosis and differential diagnosis, and attention should be paid to distinguishing pituitary adenoma apoplexy when accompanied by bleeding.